Giorgia Aureli, Fabio Colonnese, Silvia Cutarelli (eds), Intersezioni. Ricerche di Storia, Disegno e Restauro dell’Architettura, Artemide Edizioni, Roma 2020 (diségno, 2021)
Turi Sottile’s lively bright graphics on the cover (acrylic on transparent blue, 80x80 cm, 2009) are an evocative visual representation of the book’s contents. The title Lasciando aperta la porta dell’intelletto tutto può succedere (By leaving the door of the intellect open, anything can happen) conjures up the delicate, multifaceted creativity of the original and innovative nature of this study in the field of Architecture (read more).